Analisis Kelemahan Manusia Menurut Al-Qur’an - Hafifa Hafifa; Royhana Safitri; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
Human are unique, mysterious and complitated creatures. This uniqueness can be seen from its dualistic nature, such as good, bad, happy, generous, stingy, gentle, rude, diligent, lazy, and so on. This article aims to explain human weaknesses according to the koran which talks about the same theme, then discusses it systematically. The results of the research show that human weaknesses according to the koran are centered on physical reason and lust